4x²+3x-5x²+x³= 2xy•5y-3y•3x²= -7x³-5x•2x-2x•(-5)x²-6x= 33y²-17y³+y-93y²+17y³-2y=

4x²+3x-5x²+x³= 2xy•5y-3y•3x²= -7x³-5x•2x-2x•(-5)x²-6x= 33y²-17y³+y-93y²+17y³-2y=
Гость
Ответ(ы) на вопрос:
Гость
) 2 + 3x+15y = -2x - 3y    3x + 2x = -3y - 15y - 2    5x =  -18y - 2      x = (-18y - 2)/5подставим найденное значение х во 2ое уравнение:2) 3*(-18y - 2)/5 +4y = -8     (-54y - 6)/5 +4y = -8     -54y - 6 + 20y = -40     -34y = -34           y = 1  x = (-18y - 2)/5 = (-18 - 2)/5 = -20/5 = -4х = -4, y = 1
Не нашли ответ?
Ответить на вопрос
Похожие вопросы